2022
DOI: 10.3390/cancers14153829
|View full text |Cite
|
Sign up to set email alerts
|

Over-Detection of Melanoma-Suspect Lesions by a CE-Certified Smartphone App: Performance in Comparison to Dermatologists, 2D and 3D Convolutional Neural Networks in a Prospective Data Set of 1204 Pigmented Skin Lesions Involving Patients’ Perception

Abstract: The exponential increase in algorithm-based mobile health (mHealth) applications (apps) for melanoma screening is a reaction to a growing market. However, the performance of available apps remains to be investigated. In this prospective study, we investigated the diagnostic accuracy of a class 1 CE-certified smartphone app in melanoma risk stratification and its patient and dermatologist satisfaction. Pigmented skin lesions ≥3 mm and any suspicious smaller lesions were assessed by the smartphone app SkinVision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…In fact, recent studies have shown generally poor accuracy of these apps in terms of sensitivity and/or specificity in detecting skin cancer. [4][5][6] Quality, quantity and variance of image training data One of the factors that may contribute to this poor accuracy is the quality, variance and quantity of image training data used to develop and validate AI algorithms. To ensure adequate training, image data should include skin conditions relevant to the target population, along with patient-level contextual information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, recent studies have shown generally poor accuracy of these apps in terms of sensitivity and/or specificity in detecting skin cancer. [4][5][6] Quality, quantity and variance of image training data One of the factors that may contribute to this poor accuracy is the quality, variance and quantity of image training data used to develop and validate AI algorithms. To ensure adequate training, image data should include skin conditions relevant to the target population, along with patient-level contextual information.…”
Section: Discussionmentioning
confidence: 99%
“…Smartphone apps may cause significant adverse events through inaccurate predictions, which can be falsely reassuring or falsely concerning. In fact, recent studies have shown generally poor accuracy of these apps in terms of sensitivity and/or specificity in detecting skin cancer 4–6 …”
Section: Considerations Of the Task Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Some of these instruments allow a faster and more accurate diagnosis of skin neoplasms, which is necessary to ensure adequate treatment of the patient. At the same time, they require specific, lengthy training and may increase costs to health systems if used inappropriately [ 131 , 132 , 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, smartphone applications based on artificial intelligence (AI) that support skin self-exams are becoming increasingly popular [ 4 ]. Jahn et al, 2022 investigated the diagnostic accuracy of the SkinVision ® application in classifying pigmented lesions as benign or possible melanoma [ 5 ]. The sensitivity and specificity in the differentiation of nevi and melanoma were low, with 41.3–83.3% and 60.0–82.9%, respectively.…”
mentioning
confidence: 99%